Residues of 14C-malathion in stored maize grains - Sampaio, Maria Regina F. Pedral; Ruegg, Elza Flores; Bitran, Edgar A.; Abussamra, Márcia (Pesquisa Agropecuaria Brasileira, 2014)
Residues of the insecticide malathion applied to stored maize grains were determined in the laboratory by means of radiotracer techniques, which permitted the discrimination between surface residues, solvent extracted residues and bound residues. Results indicated that with time, the amount of bound and extractable residues is enhanced inside the grains from 8.9% to 14.7% while the surface residues progressively diminishes in the same period, reaching to about 50% of the applied concentration.